The Secondary School Students’ Perception Towards the English Teacher’s Strategies in Teaching Speaking On the East Coast of Peninsular Malaysia - Kamarull Ariffin, Maizurah; Yusoff, Nor Asiah; Mohamad Yusof, Nurdiyana (Selangor Humaniora Review, 2022)
Speaking is often ignored by some teachers, resulting in students’ lack of opportunities to practise English during classes and being apprehensive about utilising the language promptly. Teaching speaking is a way to provide students with knowledge on how to communicate efficiently. This research aims to identify practical speaking strategy activities based on students’ perspectives and the strategies implemented by English teachers in teaching speaking. This research uses a quantitative method that involves two sets of surveys for teachers and students. The questionnaire was distributed using an online platform called Google Form among 135 students from Pahang, Terengganu, and Kelantan, as well as among 38 English teachers as the study subjects. The data is analysed using descriptive analysis, revealing that the students prefer to use Crazy Stories and Role Play or Simulation activities as they were more effective. The teaching strategies used by English teachers contrasted as they used discussion Groups for students’ oral activities practices. The study’s findings may be a reference for future researchers to build students' confidence in speaking based on their preferred speaking activities.